(untitled) (Agricultural Engineering, 2020)
The article presents results of research on the bulk and shaken density of two commercial fertilizers: Pulgran urea and universal nitrogen fertilizer Salmag. A statistical analysis of the obtained results of average density at the assumed level of significance proved a significant difference between shaken and bulk density investigated with the use of Engelsmann apparatus and shaken density tested with a laboratory shaker for both investigated fertilizers. The obtained test results and uncertainty of the measured values served for calculation of uncertainty of the standard complex bulk and shaken density determined in case of many uncertainties. Further, an analysis of the impact of error sources on the value of complex uncertainty was conducted. The final results of the measurement were presented according to the convention of the Central Office of Measures.